2013
DOI: 10.1093/nar/gkt512
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the LINE1 ORF1 protein interactome reveals associated inhibitors of human retrotransposition

Abstract: LINE1s occupy 17% of the human genome and are its only active autonomous mobile DNA. L1s are also responsible for genomic insertion of processed pseudogenes and >1 million non-autonomous retrotransposons (Alus and SVAs). These elements have significant effects on gene organization and expression. Despite the importance of retrotransposons for genome evolution, much about their biology remains unknown, including cellular factors involved in the complex processes of retrotransposition and forming and transportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
217
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(233 citation statements)
references
References 130 publications
16
217
0
Order By: Relevance
“…In the course of their normal cellular lifecycle, TE transcripts interact with a variety of proteins, both self-encoded and host-encoded, to form a ribonucleoprotein complex (RNP) (Goodier et al 2013). RNPs, such as Alu or LINE1, have been shown to interact with a diverse range of host proteins, including chromatin modifiers, transcription factors, DNA repair factors, RNA binding proteins, and RNA Polymerase II (Mariner et al 2008;Blackwell et al 2012;Goodier et al 2013).…”
Section: Type I: Protein Interactionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the course of their normal cellular lifecycle, TE transcripts interact with a variety of proteins, both self-encoded and host-encoded, to form a ribonucleoprotein complex (RNP) (Goodier et al 2013). RNPs, such as Alu or LINE1, have been shown to interact with a diverse range of host proteins, including chromatin modifiers, transcription factors, DNA repair factors, RNA binding proteins, and RNA Polymerase II (Mariner et al 2008;Blackwell et al 2012;Goodier et al 2013).…”
Section: Type I: Protein Interactionmentioning
confidence: 99%
“…RNPs, such as Alu or LINE1, have been shown to interact with a diverse range of host proteins, including chromatin modifiers, transcription factors, DNA repair factors, RNA binding proteins, and RNA Polymerase II (Mariner et al 2008;Blackwell et al 2012;Goodier et al 2013). It is reasonable to infer that fresh insertion of TE repeats within lncRNA may confer binding to the same complexes, thereby constituting preformed protein-binding domains.…”
Section: Type I: Protein Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that phosphorylation-related proteins can be coimmunoprecipitated with ORF1p or L1 RNPs (39,40). In addition, the mitogen-activated protein kinase (MAPK) p38 has been implicated in L1 activation by environmental toxins (41,42), and its expression can be increased by exogenous ORF1p (43).…”
mentioning
confidence: 99%